THE SUCCESS FACTORS OF EXTRACT-LOAD-TRANSFORM PROCESS IN DATA INTEGRATION IMPLEMENTATION - Kamsuriah Ahmad; Siti Zarith Sofia Itmin (JOURNAL INFORMATION AND TECHNOLOGY MANAGEMENT (JISTM), 2024)
The primary purpose of data integration in data warehouse is to consolidate data from various heterogeneous data source. ETL (Extract-Transform-Load) is a traditional approach used to extract, transform and load data from external sources into data warehouse environment. Since there exists limitation on ETL approach, many organization move to ELT (Extract-Load-Transform) approach to improve the loading time and performance. To ensure the success of ELT, then identifying the factors that contribute to this success is important. Yet not many studies have been done in identifying the success factors of ELT approach in organizations so that the process can be performed efficiently and effectively. Therefore identifying the influencing factors that contribute to the success of this process is important. There are various factors proposed in previous studies; however studies focusing on identifying the success factors of ELT approach are missing and this becomes the objective of this paper. Based on the reviews, this study has collected fourteen factors where eight elements are classified under system quality factor and six elements are classified under data quality factors. All these factors will be verified by the domain experts. The success factors proposed in this study could be used as a reference to the system developers in improving the performance of data integration process.